2012
DOI: 10.1155/2012/351796
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analyses of Genes Differentially Expressed by Diet (Black Beans and Soy Flour) during Azoxymethane-Induced Colon Carcinogenesis in Rats

Abstract: We previously demonstrated that black bean (BB) and soy flour (SF)-based diets inhibit azoxymethane (AOM)-induced colon cancer. The objective of this study was to identify genes altered by carcinogen treatment in normal-appearing colonic mucosa and those attenuated by bean feeding. Ninety-five male F344 rats were fed control (AIN) diets upon arrival. At 4 and 5 weeks, rats were injected with AOM (15 mg/kg) or saline and one week later administered an AIN, BB-, or SF-based diet. Rats were sacrificed after 31 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 125 publications
(108 reference statements)
0
12
0
Order By: Relevance
“…The study was also warranted based on results from several in vivo studies suggesting that there is a diet-dependent up or down regulation of Dmbt1/dmbt1 in the liver and parts of the gut. (1820) Further, DMBT1 has been linked to liver injury and repair mechanisms concerning liver disease. (16,17) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was also warranted based on results from several in vivo studies suggesting that there is a diet-dependent up or down regulation of Dmbt1/dmbt1 in the liver and parts of the gut. (1820) Further, DMBT1 has been linked to liver injury and repair mechanisms concerning liver disease. (16,17) …”
Section: Discussionmentioning
confidence: 99%
“…(14) Furthermore, data from animal models indicate that there is a diet-dependent up or down regulation of the Dmbt1/dmbt1 expression in the liver and parts of the gut. (1820) Starting from this background the purpose of the present study was to investigate if Dmbt1 affects a Western style diet-induced liver damage in Dmbt1 knockout mice.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 4, 14 animal studies evaluated the effect of grain legume consumption on colorectal tumorigenesis using 253 animals (248 males and five females) on control diets and 355 animals (350 males and five females) on 19 different grain-legume-containing diets [78][79][80][81][82][83][84][85][86][87][88][89]. Eight diets contained whole dry beans, seven contained dry bean fractions (three fiber factions, three ethanol extract, and one ethanol extract residue); two diets each contained lentils or chickpeas, and one diet each contained black-eyed peas or dry peas.…”
Section: Grain Legumes and Colorectal Neoplasia In Animal Studiesmentioning
confidence: 99%
“…The animal studies have limitations: first, in four of the seven tumor endpoint studies, grain legumes made up the majority of the diet (45-75%; Table 4) [78][79][80]82], concentrations that are not relevant for human consumption. However, three studies showed a protective effect of the ethanol extract of navy beans fed at 10% of the diet (Table 4); the 2015 U.S. dietary guidelines for legume consumption are equivalent to ~2-5% of the diet [76], concentrations that should be evaluated in future animal studies.…”
Section: Grain Legumesmentioning
confidence: 99%
See 1 more Smart Citation